A novel total variation based ring artifact suppression method for CBCT imaging with two‐dimensional antiscatter grids. Issue 5 (20th March 2019) - Alexeev, Timur; Kavanagh, Brian; Miften, Moyed; Altunbas, Cem
Abstract : Purpose: Two‐dimensional antiscatter grids (2DASG) for cone beam computed tomography (CBCT) is a new area of research to reduce scatter intensity, and consequently improve CBCT image quality. One of the challenges in implementation of 2DASGs is their septa shadows that are impinged on the projections. If these artifacts are not corrected, they may lead to ring artifacts in CBCT images. In this work, we present a novel method to suppress ring artifacts in FPD‐based CBCT images. Methods: Briefly, our method first detects the locations of 2DASG's septa shadows in projections and then, reduces projection pixel values in septa shadows iteratively until a residual‐based convergence criterion is met. To suppress the 2DASG's septa shadows, we developed a total variation minimization (TVM) formulation, referred to as adaptive‐diffusive total variation minimization (adTVM), where the diffusivity regularization parameter was adaptively adjusted during each iteration based on the magnitude of the local pixel gradients. To test our method, we have acquired CBCT scans of phantoms using three 2DASG prototypes with different grid geometries. Projections were acquired with a linac mounted CBCT system, operated in offset detector geometry. These projections were then corrected in the following steps: first, projections were corrected using a gantry angle‐specific gain correction map; next, projections were corrected by applying our adTVM method. CBCT images were reconstructed using FDK filtered backprojection algorithm. To evaluate adTVM's performance, pixel value statistics and contrast‐to‐noise ratio (CNR) were compared in CBCT images corrected with and without our adTVM method. Results: Without our adTVM method, all three 2DASG prototypes introduced ring artifacts with varying intensities in CBCT images. With our method, significant reduction in ring artifacts was observed in all test cases. Standard deviation of CT numbers was reduced by 7–74% in uniform density phantom CBCT images, CNR was increased by 8–67%, and CT number accuracy of contrast objects embedded in the phantom was preserved. Conclusion: We propose a new method to suppress ring artifacts caused by the 2DASG's septa shadows in CBCT images. Our initial investigations indicated that adTVM method could substantially reduce such ring artifacts while preserving CT number accuracy and maintaining good spatial resolution. Therefore, our method may potentially play an important role in enabling the implementation of 2DASGs in flat panel detector based CBCT systems.